A general and efficient distance bounding protocol with multi-objective optimisation for RFID applications over a noisy channel. (17th December 2021) - Shafiee, Ebrahim; Falahati, Abolfazl
It is common to employ the distance bounding (DB) protocols to prevent relay attacks over RFID communication systems. It is impossible to utilise only one specific version of a DB protocol as a general resolution for secure identification and optimal performance due to the diversity and development of the RFID platforms such as ad hoc and IoT. Therefore, a general DB (GDB) protocol employing a multi-objective optimisation algorithm is proposed to find the appropriate GDB protocol's parameter values, increase security and reduce costs. On the other hand, reducing the false-accept probability against possible attacks increases security, and decreasing the protocol false-reject probability, runtime and memory reduces costs. The final desired optimal protocol is obtained from Pareto optimal solutions using the linear non-dimensionalisation scaling method and the LINMAP decision-making process. Introducing the figure of merit (FOM) criterion, analytical analysis, and simulation results indicate significant improvements in the protocol efficiency.